Energy-absorption characteristics of composite C-channels with different flange widths under axial compression - MOU Haolei; LIU Xingyan; LIU Bing; XIE Jiang; FENG Zhenyu (Journal of Aeronautical Materials, 2023)
Quasi-static axial compression experiments were conducted on the composite thin-walled C-channels with different flange widths. The axial compression failure modes and failure mechanisms were analyzed through CT scanning，and the effects of different flange widths on the axial compression energy-absorption characteristics of C-channels were evaluated by using the energy-absorption indexes. The single-layer shell model and multi-layer shell model of composite C-channel were established，and the finite element models were verified by comparing the failure modes，load-displacement curves and energy-absorption indexes. The results show that the flange width has a significant effect on the axial compression failure modes and energy-absorption characteristics of C-channels. The C-channels with flange widths of 25 mm and 30 mm are failed in the stable and asymptotic manner under the axial compression loads and have good energy-absorption characteristics. The deviation of mean crushing force，energy absorption and specific energy absorption obtained by the multi-layer shell model is within 5%，while that obtained by the single-layer shell model is within 8%，which indicating that the multi-layer shell model of C-channel has the higher simulation accuracy.